The application of bioactive compounds from the food industry to control mold growth in indoor waterborne coatings - Bellotti, Natalia (2013)
Microbial growth in indoor environments creates health problems, especially in people with asthma; approximately 80% of these patients are allergic to mold. Antimicrobial coatings are formulated to generate surfaces that are easy to clean and may also incorporate active agents, commonly called biocides, which inhibit microbial colonization, subsequent growth and bio-deterioration of the substrates. Some research lines seek to replace traditional organometallic and organochlorines biocides with environmentally acceptable ones. The aim of this research was, primarily, to explore the possible application of different compounds used in food industry like preservatives to be used as antimicrobial additives for antimicrobial coatings. Four biocides were tested against two different ambient molds isolated from an interior painted wall (Chaetomium globosum and Alternaria alternate). The selected biocides were zinc salicylate, zinc benzoate, calcium benzoate and potassium sorbate. The resulting paints were subjected to biological and physical tests (viscosity, hiding power, humidity absorption and biocides leaching rate). Bioassays revealed that zinc benzoate and zinc salicylate resulted active against both fungi.